Social Capital and the Use of Dual Currency at the Border (A Case Study of Economic Activities on Sebatik Island): Kapital Sosial dan Penggunaan Mata Uang Ganda di Perbatasan (Studi Kasus Kegiatan Ekonomi di Pulau Sebatik) - T, Nurlinda; Birsyada, Muhammad Iqbal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Sebatik Island is located in North Kalimantan Province and is a border area of the Unitary State of the Republic of Indonesia (NKRI) and the outermost region of Indonesia. This island is controlled by two countries, namely the northern part of Sebatik is controlled by the Kingdom of Malaysia and the southern part of Sebatik is controlled by the Republic of Indonesia with the separation of the territory using the coordinate point 4°10' according to the London Convention of 1891. This island is known as a border area, the outermost island of Indonesia, and the foremost island of the NKRI. The Sebatik community has local wisdom where in this region there are two currencies used by the community as a means of buying and selling transactions, namely the Malaysian Ringgit and the Indonesian Rupiah. This research employs a qualitative strategy through the use of case study technique. The data gathering process is carried out by observation, in-depth interviews, and documentation. This investigation employs data reduction, data display, and conclusion drafting as its data analysis approach. The findings of this investigation show that the life of the Sebatik community is a life that is typical of the Malindo (Malaysia – Indonesia) cross-border and various types of goods are traded between Sebatik Indonesia and Tawau Malaysia and this economic activity has been well established for decades and has become a mutual symbiosis between these two regions.